Moving beyond species: fungal function in house dust provides novel targets for potential indicators of mold growth in homes - Neeraja Balasubrahmaniam; Jon C. King; Bridget Hegarty; Karen C. Dannemiller (Microbiome)
Abstract Background Increased risk of asthma and other respiratory diseases is associated with exposures to microbial communities growing in damp and moldy indoor environments. The exact causal mechanisms remain unknown, and occupant health effects have not been consistently associated with any species-based mold measurement methods. We need new quantitative methods to identify homes with potentially harmful fungal growth that are not dependent upon species. The goal of this study was to identify genes consistently associated with fungal growth and associated function under damp conditions for use as potential indicators of mold in homes regardless of fungal species present. A de novo metatranscriptomic analysis was performed using house dust from across the US, incubated at 50%, 85%, or 100% equilibrium relative humidity (ERH) for 1 week. Results Gene expression was a function of moisture (adonis2 p < 0.001), with fungal metabolic activity increasing with an increase in moisture condition (Kruskal–Wallis p = 0.003). Genes associated with fungal growth such as sporulation (n = 264), hyphal growth (n = 62), and secondary metabolism (n = 124) were significantly upregulated at elevated ERH conditions when compared to the low 50% ERH (FDR-adjusted p ≤ 0.001, log2FC ≥ 2), indicating that fungal function is influenced by damp conditions. A total of 67 genes were identified as consistently associated with the elevated 85% or 100% ERH conditions and included fungal developmental regulators and secondary metabolite genes such as brlA (log2FC = 7.39, upregulated at 100% compared to 85%) and stcC (log2FC = 8.78, upregulated at 85% compared to 50%). Conclusions Our results demonstrate that moisture conditions more strongly influence gene expression of indoor fungal communities compared to species presence. Identifying genes indicative of microbial growth under damp conditions will help develop robust monitoring techniques for indoor microbial exposures and improve understanding of how dampness and mold are linked to disease. Video Abstract